Gasiang Tangkurak/Sirompak Sebagai Inspirasi Karya Musik Dalam Seni Pertunjukan Tradisi Minangkabau - Muhammad Arianda; Yensharti Yensharti (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find sirompak music as a traditional Minangkabau music performance that uses gasian tangkorak as inspiration for making works. characteristic and gives rise to cobs/sirompak as the inspiration for saluang music. This type of research is qualitative with descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques were carried out by literature study, observation, interviews and documentation. Data analysis techniques are carried out by collecting data, describing data and concluding data. Based on the results of the study, it was shown that the traditional sirompak art which contained magical elements was still displayed in public places and with the same intent and purpose during the Animist era, it would cause disunity against families or neighbors, because of their intentions. and sirompak's aim was not good at that time. . After turning into a traditional art, there are elements of lyrical music and dance in this sirompak art, and the role of gasiang skulls in sirompak music is very influential in it because the hallmark of sirompak music itself is a top made of a human head skeleton. , but now the top has been replaced with the top made of coconut shells which are shaped in such a way as to be similar to the original.